Informasi Laba, Aliran Kas dan Harga Saham dalam Kaitannya dengan Siklus Hidup Perusahaan - Suyanti, Ni Wayan Ade; Ariyanto, Dodik; Sudana, I Putu; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi, 2022)
This study aims to examine the effect of earnings information on stock prices in relation to the company's life cycle at the growth, mature and decline stages. This research was conducted in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 using secondary data, namely the company's annual report. The method of determining the sample using purposive sampling method. The data analysis technique used is multiple linear regression. The results of the analysis show that the company's profit information during the growth and mature stages has a positive effect on stock prices while at the decline stage it has a negative effect. Information on the cash flow of the company's operating activities during the growth, mature and decline stages has a positive effect on stock prices. Information on the cash flow of the company's investment activities during the growth and mature stages has a negative effect on stock prices while at the decline stage it has a positive effect. Information on the cash flow of the company's funding activities during the growth, mature and decline stages has a positive effect on stock prices. Keywords : Profit Information; Cash Flow; Stock price; Company Life Cycle.